EC proposes to establish an entry-exit system. (May 2016) - Unknown
Abstract : The European Commission has presented revised proposals for an entry-exit system to speed up, facilitate and reinforce border check procedures for non-EU nationals travelling to the EU. This is part of the broader 'Smart Borders Package', addressing the role of information systems in enhancing external border management, internal security and the fight against terrorism and organised crime.